Scream of the evil genie #13 - Stine, R. L. (New York : Scholastic, 1997)
When a genie named Jenna pops out of a soda can and offers you three wishes, you think all your dreams have come true. But Jenna has a few tricks up her sleeve. If you don't watch out, the wishes of your dreams could turn into a nightmare.
"An Apple paperback."
"A Parachute Press book"--T.p. verso.
RL: 4.
008-012.
Keywords: Plot-your-own stories -- Juvenile fiction; Horror stories